Inclusion of the Public in the Natural Capital, Ecosystem Services and Green Infrastructure Assessments (Results of Structured Interviews with Stakeholders of Commune Liptovská Teplička) - Moyzeová Milena (Ekológia (Bratislava), 2018)
Nowadays, topics like natural capital assessment, ecosystem services and green infrastructure have become frequent subjects of a number of national and international projects accomplished on local, regional, national and cross-frontier levels. These projects respond to the deterioration of biotopes due to their fragmentation and degradation as a result of constructions and tourism/recreation. This situation requires an economic assessment of ecosystems from the view point of their capacities to satisfy human necessities with simultaneous conservation of the environmental quality, and the optimal status of landscape diversity both in rural and urban areas. The aim of the Green Infrastructure initiative is to stop the loss of land as an irreplaceable natural resource and to contribute to the inclusion of ecological and sustainability aspects into the spatial planning and regional development in rural and urban areas. Green Infrastructure is the tool that may reduce the loss of ecosystem services connected with future occupation of land and improve functions of land. It may support ecological measures aimed at conservation of agricultural landscape and adoption of measures in the sphere of forest and water economies. Important role in the assessment of ecosystems is played not only by the scientists but also by experts and the public at large. This is the reason why ever more stakeholders possessing knowledge of local territory and personal life experience participate in these projects. Their judgments and views, often bearing information important for the above-mentioned assessment, are applied to proposed measures aimed at the improvement of environmental quality and quality of life in terms of sustainability. This article brings the possible example of how to include a selected sample of stakeholders into the assessment of natural capital and ecosystem services on local level in the frame of Green Infrastructure. The aim of this paper is to analyse attitudes of the involved for the evaluation of natural capital and ecosystem services at a local level by means of structured interviews. Obtained views will be applied for the assessment of ecosystem services and proposals aimed at protection and conservation of natural capital and building of green infrastructure. The research was carried out in the model territory of the rural commune Liptovská Teplička.